Pharmacognostical and Phytophysicochemical investigations of Trigonella foenum – graecum Linn - Thorat, R. M.; Gaikwad, D.D. (Journal of Drug Delivery and Therapeutics, 2019)
Fenugreek (Trigonella foenum-graecum L.), plant is distributed throughout the world and which belongs to the family Fabacecae. The fenugreek seed contains active constituents such as Carbohydrates, Proteins, Alkaloids, Flavonoids, Free amino acids, Saponins, Glycosides, Vitamins, Minerals, Mucilage, Fixed Oils & Volatile Oils etc. It has been commonly used as a traditional food and medicine. Fenugreek is known to have hypoglycemic, and hypocholesterolaemic effects, Anti-inflammatory effects. Fenugreek has potential for curing diseases and also as a source for preparing raw materials of pharmaceutical industry like in steroidal hormones. This review gives view mainly on the Morphological evaluation, Microscopic evaluation, Physicochemical evaluation, Fluorescence Analysis and Phytochemical evaluation. Keywords: Trigonella Foenum-groecum L., Seeds, Fabacecae, Saponins.